Uji Performansi Pencuci Biodiesel Metode Pengkabutan Air Dalam Minyak - Argo, Bambang Dwi; Djoyowasito, Gunomo; Yulianingsih, Rini (Rekayasa Mesin, 2010)
Washing of biodiesel removes contaminants (soap, catalyst, methanol and free glycerin) from biodiesel, even though this activity will sometimes cause an emulsion. This research aims to develop new method of washing that can minimize emulsification. The method used is misting water in crude biodiesel by certain nozzle. Washing apparatus has 5 main part i.e. nozzle, washing chamber, circulation pump, valve to set level of debit and piping channel. The research has been done to study dependency of biodiesel washing on the numbers of nozzles (2, 3 and 4) , the distance between nozzle and constrictor plate (2 cm, 4 cm, 6 cm and 8 cm) and the level of wash water debit 45.3 ml/min,83.6 ml/min and 150 ml/min . Parameters measured were pH of wash water, emulsion formed, rendemen of biodiesel, quality of biodiesel and energy consumption. Variation of the numbers of nozzles are purposed to have more extensively contact between water and biodiesel. At optimum level of debit, high performance biodiesel washing expeted, with little emulsion can be obtained. The research indicates that the numbers of nozzles, the distance of nozzle and level of water debit are significant variables to determine washing performance. The research showed that washing biodiesel with the numbers of nozzles 4 pc, debit of washing water 83.6 ml/min and 45.3ml/min and distance between nozzle and constrictor plate 8 cm produce 100 % biodiesel for every step washing, with pH of washing water at third washing 7.1 and emulsion formed 81.6 ml . Misting water in oil method needs smaller energy than others, i.e. only 4% of stirrer method and 1.2% of bubble method. Quality biodiesel – i.e. density, flash point, cetane index, cloud point, moisture content, viscosity – meets ISO standard. Keywords : Biodiesel, Washing, Emulsification, Energy